Desarrollo de una aplicación SCADA para el control de nivel de un proceso simulado de tres tanques en cascada. - Guacapiña Toapanta, Diego Vicente (2021)
This technological proposal aims to implement a control system based on classic PID controllers in a level control process of three cascade tanks that will be simulated in a specific software; this control system will be executed by a simulated programmable automaton; a control algorithm will be previously loaded into it, in this way getting a control in the liquid level variable for each tank; this process will be monitored through an SCADA application implemented in a data processing and visualization software that the PLC throws, such application allows the user to create a data record in a spreadsheet for further analysis of system behavior; using the TCP/IP communication protocol it is possible to create an OPC server that allows the two-way transmission of data so that the user can have manual and automatic control of the process. With the realization of this project Electromechanical Engineering students can develop practices that allow to reinforce knowledge in fields such as: process modeling, communication networks, automaton programming and HMI interface design.